Antibiotics in Milk and the Risk of Drug Resistance - Jawahir A. Mokhtar (Journal of King Abdulaziz University: Medical Sciences, 2024)
The mammary glands of all mammals produce a biological fluid after giving birth known as milk. Intrinsic factors impacting drug transition to milk include animal breed, species, milk protein, fat content, and lactation period. Environmental conditions, disease, drug solubility, and drug-to-drug interaction are the extrinsic factors. Antibiotics are an important factor in animal feed production. Antibiotics are mainly administered in animals for disease prevention, treatment, and growth promotion. Antibiotic residues could be detected in animal products such as meat, egg, and milk. The side effects of antibiotic residues include immunopathological effects, antibiotic-resistant bacterial transfer to humans, allergy, nephropathy (gentamicin), mutagenicity, reproductive disorders, bone marrow toxicity (chloramphenicol), hepatotoxicity, and carcinogenicity (oxytetracycline, sulphamethazine, and furazolidone). Antibiotic-resistant bacterial transfer to humans because of the resistance mobile properties is the most important detrimental impact. This review addresses the antibiotics pharmacology in milk and the side effects of their residues on human health.